Antioxidant activity of Juglans regia L. and Rumex obtusifolius L. leaf extracts and screening for their allelopathic potential - Đorđević, Tijana; Gajić Umiljendić, Jelena; Sarić-Krsmanović, Marija; Radivojević, Ljiljana; Đurović-Pejčev, Rada; Stevanović, Marija; Vuković, Mara (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
Secondary plant metabolites with allelopathic activity or phytotoxicity could be biotechnologically important, serving as a source of allelochemicals, and thus contributing to the agro-industrial sector. The objective of this study was to use the obtained common walnut (Juglans regia L.) and bitter dock (Rumex obtusifolius L.) leaves extracts rich in phenolic compounds, i.e. with high antioxidant potential, and to identify their phytotoxicity to Setaria glauca (L.) P. Beauv. and Sorghum halepense (L.) Pers. weed seedlings grown in vitro. The obtained plant extracts had remarkably high affinity for scavenging free radicals, having DPPH IC50 values of 0.127 mg/ml for common walnut leaf extract and 0.194 mg/ml for bitter dock leaf extract. Ferric reducing antioxidant power of the extracts was also high, FRAP value of the common walnut leaf extract was 384.4 ± 8.1 μmol Fe2+/g dry mass, and of the bitter dock leaf extract 321.6 ± 2.5 μmol Fe2+/g dry mass. At the highest used concentration, common walnut leaf extract reduced germination of S. glauca by 67.3%, while bitter dock leaf extract reduced germination of that weed by 54.5%. Shoot length of S. glauca was inhibited 80.7% when subjected to common walnut leaf extract, and 78.2% under the influence of bitter dock leaf extract, and its root length was inhibited 96.4% and 93.1% respectively. Germination of S. halepense was inhibited 100% under the influence of the obtained common walnut leaf extract at its highest test concentration, and 79.2% when subjected to bitter dock leaf extract at the same concentration. Shoot length of this weed was reduced 100% after treatment with common walnut leaf extract, and 93.7% when subjected to bitter dock leaf extract. Root length was reduced 100% and 99.3%, respectively. Overall, the extracts demonstrated pronounced antioxidant activity and remarkable allelopathic potential.